2023
DOI: 10.1186/s12903-023-02935-x
|View full text |Cite
|
Sign up to set email alerts
|

A large-cohort study of 2971 cases of epulis: focusing on risk factors associated with recurrence

Abstract: Background To analyze the clinicopathological features of different histological subtypes of epulis, and evaluate the risk factors associated with recurrence. Materials and methods A retrospective study including 2971 patients was performed. The patients’ sex, age, location, size, histological subtypes, recurrence information, oral hygiene habits, periodontitis symptoms and smoking history were retrieved from the patient medical records and follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Most cases of pregnancy‐related gingival overgrowth would resolve fully or reduce in size after 6–8 weeks postpartum 29,41 . Zhao et al reviewed 2917 cases of fibrous epulis and reported an average recurrence rate of 11.28% with pregnancy‐related lesions having the highest recurrence rates 42 . Furthermore, Zhao et al concluded that regular periodontal supportive therapy and management of the periodontal inflammation had a significant impact in reduction the recurrence rates 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cases of pregnancy‐related gingival overgrowth would resolve fully or reduce in size after 6–8 weeks postpartum 29,41 . Zhao et al reviewed 2917 cases of fibrous epulis and reported an average recurrence rate of 11.28% with pregnancy‐related lesions having the highest recurrence rates 42 . Furthermore, Zhao et al concluded that regular periodontal supportive therapy and management of the periodontal inflammation had a significant impact in reduction the recurrence rates 42 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 41 Zhao et al reviewed 2917 cases of fibrous epulis and reported an average recurrence rate of 11.28% with pregnancy‐related lesions having the highest recurrence rates. 42 Furthermore, Zhao et al concluded that regular periodontal supportive therapy and management of the periodontal inflammation had a significant impact in reduction the recurrence rates. 42 This emphasizes the point raised in the current case report where local periodontal debridement should have been performed after the first excisional biopsy in order to reduce the chances of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the variable used terminologies, most of the previous studies have agreed with our nding that irritational broma is the most prevalent (40%). However, they reported different percentages 57.4%(Reddy et al, 2012), 69.3%(Vidyanath et al, 2015), 47%(Babu and Hallikeri, 2017), 37.4%(Sangle et al, 2018), 72.09%(Dutra et al, 2019) and 61%(Zhao et al, 2023). On the contrary, few research showed that pyogenic granuloma is the most common ORHL, followed by irritational broma(Kashyap et al, 2012 andKadeh et al, 2015).In line with our results, Naderi et al (2012), Reddy et al, (2012), Babu and Hallikeri (2017) and Dutra et al (2019) have shown that pyogenic granuloma is…”
mentioning
confidence: 99%